STUDY THE EFFICACY OF CHRONIC INTERMITTENT INTRAVENOUS INSULIN INFUSION THERAPY OVER AND ABOVE CONVENTIONAL TREATMENT IN PATIENTS OF DIABETIC AUTONOMIC NEUROPATHY - Pk, Maheshwari; Agrawal, Prabhat; Prakash, Prashant; Ak, Singh; Bansal, Saurabh; Purohit, Deepak; Agarwal, Shweta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aims to emphasize the importance of chronic intermittent intravenous insulin infusion therapy (CIIIT) over and above conventional treatment in patients with diabetic autonomic neuropathy. Methods: In our study, we had 50 patients; most of the patients were in the age group of 30–50 years and sex ratio for male:female was 3:2. The patients were divided into two groups. One group which received monthly CIIIT for 8 h per month for 6 months (Group-1) whereas other group did not receive it (Group-2). However, both groups continued their old treatment (oral hypoglycemic or subcutaneous insulin). Results: On 12-month follow-up, in Group-1, palpitation improved in 16 of 17 (94.1%), giddiness improved in 12 of 20 (60.0%), constipation improved in 7 of 12 (58.3%), diarrhea improved in 7 of 8 (87.5%), erectile dysfunction improved in 3 of 5 (60.0%), abdominal fullness improved in 12 of 17 (70.5%), and abnormal sweating improved in 6 of 20 (30%). In comparison to this, in Group 2, palpitation improved in 6 of 19 (31.5%), giddiness improved in 2 of 15 (13.3%), constipation improved in 3 of 13 (23.0%), diarrhea improved in 3 of 7 (42.8%), erectile dysfunction improved in 3 of 5 (20.0%), abdominal fullness improved in 4 of 13 (13.7%), and abnormal sweating improved in 5 of 17 (29.4%). Conclusion: At the conclusion of our study, we found that patients, who were previously refractory to conventional pharmacotherapy, showed a considerable response to CIIIT with most patients giving a history of improvement in their symptoms after therapy and during follow-up. Therefore, it is recommended that patients presenting with complaints of diabetic autonomic neuropathy should be managed by CIIIT rather than the conventional pharmacological therapies.